Demographics and Cycle Outcomes of Transgender Patients Accessing Gamete Services at Monash IVF Victoria - Phillippa CLEMENTS; Mark P GREEN; Deirdre ZANDER-FOX; Gareth WESTON; Rita ALESI (Fertility & Reproduction, 2022)
Background: Since 2003 an increasing number of transgender patients are electing to store gametes prior to transitioning and/or utilising ART services at Monash IVF Victoria. Aim: The aim of this study was to determine the number of transgender patients accessing gamete storage and utilisation services, as well as their cycle outcomes. Methodology: A retrospective study of frozen gamete usage of 48 patients collected between 2003-2021 was undertaken. Results: Trans-female patients were the most common cohort, with 37 patients (16-49yrs, mean age 25.9± 7.7) undertaking semen freezing and two (13yrs and 17yrs) surgical sperm retrieval prior to transitioning. Between 2003-2010 and 2011-2021 six (15.4%) and 33 (84.6%) patients respectively used this treatment. On average 2.3± 2.0 ejaculates/patient were frozen. At freezing 13 (35.1%) patients had >1 ejaculate with a low sperm count and 23 patients (62%) low sperm motility compared to WHO criteria; data were unavailable if patients had already commenced hormonal therapy. Four patients (10.8%) elected to register as sperm donors and their sperm used, while only four (10.8%) trans -female patients have returned, 2-7 years later (mean 5.3± 2.2 years) with a cis -female partner to utilise their gametes; two achieving a live birth. In contrast, nine trans -male patients (20-29yrs, mean age 23.9± 2.6yrs) undertook oocyte collection; one (11.1%) had treatment in 2003-2010 and eight (88.9%) between 2011-2021. On average 1.4± 0.7 egg freezing cycles/patient were conducted, with 4-30 eggs frozen/collection (mean 14.4± 7.1). One patient donated their oocytes to their cis- female partner in an ICSI cycle 7 years after freezing and achieved one live birth. Conclusion: Gamete cryopreservation is a valuable service for transitioning patients wishing to preserve fertility; numbers are increasing, with low utilisation to date and successful outcomes recorded. Exploring transgender patient experiences and ART service uptake will provide vital feedback to tailor an inclusive fertility journey at our clinics.